The social consequences of climate change : debates in research and policy - Açikalin, Suay Nilhan; Erçetin, Şefika Şule (Emerald Publishing Limited, 2024)
Tackling a global and seismic problem such as climate change requires an equally extensive approach. Investigating current scientific knowledge about climate change in public and policy discussions, as well as the connections between social, economic, and political discourse, The Social Consequences of Climate Change takes a take a multifaceted approach to one of the biggest challenges of our time. Understanding the role of climate conditions in all aspects of human society - where we live, how we build, how we move - chapters wield relevant approaches and techniques from across disciplines to reframe issues that are essential to improving sustainability and capturing innovative solutions to the climate problem. Covering the role of businesses in combatting climate change, environmental health, the vulnerability of urban communities, the nexus between climate, economy and society, climate and national and international agendas, and more, the authors clarify both scientific and policy arguments about the social repercussions of climate change to offer a working basis for seeking solutions. A rich collection of reflections from across the social sciences, this is vital reading for researchers and policymakers invested in how best to respond to a world of increasing climate extremes.
Keywords: Climatic changes -- Social aspects.; Climatic changes -- Research.; Climatic changes -- Government policy.; Social Science -- Sociology -- Urban.; Climate change.; Urban communities.; elektronické knihy; electronic books